2020
DOI: 10.1186/s12889-020-09450-6
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities and risk factors analysis in prevalence and management of hypertension in India and Nepal: a national and subnational study

Abstract: Background: Hypertension is one of the leading risk factors for cardiovascular diseases in India and Nepal. Socioeconomic disparity in these two countries has created wide gap in management of hypertension. However, inequalities in prevalence and management (awareness, treatment, and control) of hypertension is poorly assessed. This study analyzes the risk factors associated with prevalence and management of hypertension in India and Nepal and assesses the wealth-and education-based inequalities in them. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 42 publications
1
16
1
Order By: Relevance
“…However, contrastingly, in our study, the uncontrolled or under-treated hypertension was found to be higher in the urban areas by 7.2 percentage points. Our study corroborates with the findings of previous studies that wealth and education are important determinants in both control and treatment of hypertension [50]. Studies have found that sedentary lifestyle and unhealthy eating habits are higher in urban areas leading to obesity and eventually results in uncontrolled hypertension despite treatment [51,52].…”
Section: Discussionsupporting
confidence: 92%
“…However, contrastingly, in our study, the uncontrolled or under-treated hypertension was found to be higher in the urban areas by 7.2 percentage points. Our study corroborates with the findings of previous studies that wealth and education are important determinants in both control and treatment of hypertension [50]. Studies have found that sedentary lifestyle and unhealthy eating habits are higher in urban areas leading to obesity and eventually results in uncontrolled hypertension despite treatment [51,52].…”
Section: Discussionsupporting
confidence: 92%
“…6 Sabapathy et al included school-children of Bangalore, south India, in their study and found that prevalence of prehypertension and hypertension was 2.7% and 3.2%, respectively. 7 Compared with this, overall prevalence of hypertension among adults in India was 11.4% (95% confidence interval [CI], 11.4-11.5) as shown by Rauniyar et al 8 Our study aims to determine the prevalence of prehypertension and hypertension in the community levels of India in the eastern parts, which has not been documented on a large scale, and identify its contributing factors, which would establish an early prevention program in the long run.…”
Section: Introductionmentioning
confidence: 76%
“…Previous studies examining the prevalence of NCDs using nationally representative datasets such as the Nepal Demographic and Health Survey 2016 (NDHS) have identified high burden PLOS GLOBAL PUBLIC HEALTH of hypertension in Nepal [13,21]. However, NHDS does not disclose the specific population groups and their sample sizes, which makes it difficult to determine the prevalence of NCDs in a particular population group within Nepal.…”
Section: Discussionmentioning
confidence: 99%